Nursing care for a patient with intracerebral hemorrhage complicated with toxic epidermal necrolysis: a case report - Zhang, Doudou; Zhang, Qiuping; Li, Hanhua; Lai, Wen; Chen, Pingyun (Frontiers in Medicine, 2025)
This study summarizes the nursing care for a patient with intracerebral hemorrhage complicated with toxic epidermal necrolysis, focusing on infection prevention and control. Advanced health assessment showed that the primary nursing issue was a high risk of infection. Nursing interventions were implemented to prevent and control infection in various systems, emphasizing four key aspects: respiratory management after tracheostomy, lumbar cistern drainage care, skin management, and nutritional support. The patient’s skin healed, infection indicators decreased, and no secondary infections occurred. On the 24th day after admission, the patient was transferred to the neurosurgery department for ventriculoperitoneal shunt surgery. The patient was transferred to a rehabilitation hospital 21 days after surgery.